Upgrading brown grease for the production of biofuel intermediates. (February 2020) - Spiller, Ryan; Knoshaug, Eric P.; Nagle, Nick; Dong, Tao; Milbrandt, Anelia; Clippinger, Jennifer; Peterson, Darren; VanWychen, Stefanie; Panczak, Bonnie; Pienkos, Philip T.
Abstract: Products from waste streams can reduce the amount of materials going to landfills or being incinerated. Brown grease captured from grease traps or wastewater facilities is produced at approximately 1, 500, 000 metric tons annually in the United States. Two brown grease samples were characterized from a local collector. Raw brown grease was fermented using Clostridium butyricum to produce butyric acid, achieving a yield of 0.55 butyric acid/g sugars indicating that glycerol and lactic acid were also converted. Hexane extraction of the fermentation broth gave an 81.3% recovery of lipids. Techno-economic analysis calculated a minimum fuel selling price of $1.81 per gallon gasoline equivalent (GGE) for a facility based on a city the size of Denver and a brown grease delivery price of $100 per dry metric ton. Exploiting waste streams as feedstocks can significantly reduce costs to produce fuels and can be brought to scale more rapidly due to their ready availability. Graphical abstract: Unlabelled Image Highlights: Pretreatment is not necessary for effective fermentation and extraction of lipids. High yields of butyric acid indicate products formed from glycerol and lactic acid. Three hexane extractions of raw brown grease achieved an 82% recovery of lipids. Minimum fuel selling price of $1.81/GGE was estimated at delivery costs of $100/ton.